CONSUMER INVOLVEMENT IN THE VALUE CHAIN AS A MANAGEMENT INSTRUMENT OF INNOVATION PROCESSES IN A BISINESS ENVIRONMENT - T. N. Zhukova (Дискурс)
The article discusses the trends in the innovation process management at the enterprise connected with the concept of "open innovation". The author shows the value-based approach role in the organization of innovative activity of the company. The paper describes the factors involving consumers in the creation of a new consumer value. The article defines prospects and problems of the company that arise with consumers' involvement in the process of innovation. The author classifies the forms of consumer involvement in the innovation process. The article highlights a company's goals for creating a system of consumer involvement in the development and improvement of new products.